Improving statistics and indicators on women using household surveys - Naciones Unidas (Nueva York, N.Y. : Naciones Unidas, 1988)
Survey planning and operation--Role of household surveys in improving statistics and indicators on women--Stages of work in planning and conducting a household survey in which the situations of women and men are recorded with equal accuracy--Designing the questionnaire--General principles of questionnaire desing--The household--Education and training--Economic and other activities--Measures of income and well-being--Meausures of well-being in other fields--Migration.
Keywords: INDICADORES SOCIALES; ENCUESTAS; JEFAS DE HOGAR